2020
DOI: 10.1136/bmjgh-2019-001814
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in the incidence and safety of abortion in Nigeria

Abstract: BackgroundWe know little about the frequency, correlates and conditions under which women induce abortions in Nigeria. This study seeks to estimate the 1-year induced abortion incidence and proportion of abortions that are unsafe overall and by women’s background characteristics using direct and indirect methodologies.MethodsData for this study come from a population-based, nationally representative survey of reproductive age women (15–49) in Nigeria. Interviewers asked women to report on the abortion experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 26 publications
7
74
0
Order By: Relevance
“…Prior research has indicated that women in their peak reproductive years, urban residents, and more educated women tend to have more abortions, and we expect similar results in Rajasthan (Bell et al. 2020; International Institute for Population Sciences (IIPS) and ICF, 2017; Singh et al. 2017).…”
Section: Introductionsupporting
confidence: 60%
“…Prior research has indicated that women in their peak reproductive years, urban residents, and more educated women tend to have more abortions, and we expect similar results in Rajasthan (Bell et al. 2020; International Institute for Population Sciences (IIPS) and ICF, 2017; Singh et al. 2017).…”
Section: Introductionsupporting
confidence: 60%
“…This could be due to better educated women may have improved access to health information [35] and thus, better knowledge of the abortion law [36]. Similarly, the evidence provided by other studies from Ghana [29,36,37], Nigeria [38], Kenya [39], Iran [40] have shown that better educated women had higher odds of having an induced abortion compared with less educated women. The other possible reasons for higher odds of induced abortion among more educated women may be attributed to their employment status and lack of time to care for children [41], wanting to postpone/space childbirth [27], and more tendency to plan their family size [42].…”
Section: Discussionmentioning
confidence: 87%
“…It is recognized that about 10 -15% of all pregnancies end in spontaneous abortion, [15] and another proportion is willfully terminated due to unintended pregnancy; for instance, rates of 33 to 46 induced abortions per 1,000 women of reproductive age group were reported in Nigeria. [16,17] It is noteworthy that either of these categories can end in incomplete abortion with the attendant morbidities and mortality when not managed appropriately. Thus, the need for a more convenient, affordable, and nonsurgical treatment method in our environment cannot be over-emphasized.…”
Section: Discussionmentioning
confidence: 99%